10.4: Leakage‐free solution organic light‐emitting diode using ternary host with single‐diode emission area up to 6×11.5 cm2. (4th October 2019) - Liao, Si-Yi; Su, Hsiao-Tso; Hsiao, Yung-Hung; Chang, Yu-Fan; Chang, Chiung-Wen; Niu, Mu-Chun; Meng, Hsin-Fei; Yen, Chun; Chao, Yu-Chiang; Chang, Chih-Yu; Zan, Hsiao-Wen; Horng, Sheng-Fu
Abstract : The electrical current leakage and stability are studied for solution OLED with areas of 4.45 mm 2, 3×3.2 cm 2, and 6×11.5 cm 2 . All organic layers are deposited by blade coating and initial current leaking defects can be avoided by careful control of the coating conditions. The detrimental burning point caused by a local current short developed after long‐time operation can be avoided by reducing the operation voltage using ternary mixed host. Furthermore, the crystallization defect is reduced by the ternary host. For orange device the binary host is good enough. For area as large as 6 × 11.5 cm 2 the OLED no burning point after an operation over 1600 hours.